Relações diálogicas entre Alberto Caeiro e Manoel de Barros - Marques, Luis Paulo Fiúza (2014)
This dissertation aims at analyzing the convergence and divergence between Alberto Caeiro’s poetry, through the book O guardador de rebanhos, and Manoel de Barros’s poetry, through the book O livro das ignorãças, and through the lens of some concepts belonging to the philosophy of language, specially dialogism, comparative literature, and literary theory. We seek to comprehend how these areas of knowledge contribute to the analysis and interpretation of the aforementioned works, and also to the understanding of the dialog between these poetic texts. The adopted methodology consisted of a thorough and critical reading of Manoel de Barros’s Poesia completa, from which we have selected O livro das ignorãças, published in 1993. We strongly believe that this work establishes a relevant dialog with the poetry of Alberto Caeiro, and that the comparative study between both texts not only contributes but also enlarges the knowledge on how O guardador de rebanhos defines itself as interdiscourse in the Brazilian writer’s poetry. Having chosen the books, the next step was to define our objectives according to each poem, taking into consideration the topics of philosophy of visible, negation of thinking, and the nature and perception of God or religiosity. Alberto Caeiro’s poem V and poem XLVI, and the poem Uma didática da invenção have been selected as key but not exclusive texts in their close intertextual relation with the idea of world experience presented by the poets. Regarding the theoretical basis guiding this dissertation, we have selected the theories proposed by Mikhail Bakhtin, Leyla Perrone-Moisés, Wolfgang Kayser, Antonio Candido and Sandra Nitrini. The results obtained by this research show possible influences of Alberto Caeiro’s positioning towards existence in Manoel de Barros’s poerty.